2015
DOI: 10.1007/s10901-015-9442-9
|View full text |Cite
|
Sign up to set email alerts
|

In-between spaces and social interaction: a morphological analysis of Izmir using space syntax

Abstract: This research tackles the intermediate spaces between buildings and the street, by examining the definition and importance of spatial configuration in relation to urban morphology and social relations. It also analyses how the organisation of in-between space affects social interaction in different urban forms. To understand the complex relations and socio-spatial structure of the city, it is important to use mixed methods. This research utilises various methods to focus on three dissimilar urban morphologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 26 publications
1
57
1
2
Order By: Relevance
“…The negative relationship between circulation planning and social interaction ( Figure 9) seems to be in contradiction to some studies [30,34,35]. Since community scales in Taiwan are relatively small, circulation and accessibility of the community imply more externally rather than internally.…”
Section: The Canonical Functions Betwwen Planning Factors and Place Rcontrasting
confidence: 60%
See 1 more Smart Citation
“…The negative relationship between circulation planning and social interaction ( Figure 9) seems to be in contradiction to some studies [30,34,35]. Since community scales in Taiwan are relatively small, circulation and accessibility of the community imply more externally rather than internally.…”
Section: The Canonical Functions Betwwen Planning Factors and Place Rcontrasting
confidence: 60%
“…A handful of studies have investigated features of the built environment at the smaller site scale. These studies have revealed that social interaction can be enhanced through the presence of outdoor courtyards [34], common gardens [35], and trees and grass [36,37] in apartment complexes and public housing communities, and also front porches and narrow setbacks in traditional community layouts [28,38,39]. Research concerning factors that enhance community participation has concentrated on individual characteristics, such as socioeconomic and demographic variables, or social networks and shared norms [10,40,41].…”
Section: Physical Environment and Social Interactionmentioning
confidence: 99%
“…Hillier and Iida (2005) measured the correlation between measurements of space syntax and pedestrian traffic to identify, from a geometric and topological perspective, how the spatial configuration of street networks influences the movement flows of cities, thus affecting the evolution of land-use patterns [30]. Additionally, Can and Heath (2016) showed that spatial configuration influences social activities by examining the importance of the configuration related to urban morphology and social relations [31].…”
Section: Analytical Formulamentioning
confidence: 99%
“…The old urban fabric and its morphologies were, formally or informally, influenced by the wave of modernism and replaced later by the new urban context, which resulted in the loss of the relationship between built forms and streets [36]. The urban renewal operation that took place as a part of a comprehensive development plan in Baghdad critically recognised the old urban fabric and determined an efficient process to preserve this vital sector of the city.…”
Section: The Old Fabric and The Modern Trendmentioning
confidence: 99%